Agente etiológico de sepsis neonatal en el Hospital Isidro Ayora de Loja en el periodo enero 2015 a junio 2016. - Rubio Medina, Annie Catherin (2017)
The neonatal sepsis is a clinical picture derived from the invasion and proliferation of bacteria, virus and fungi in the newborn’s bloodstream, which is generally apparent within the first 28 days of life. The study presented hereby was of descriptive, retrospective. It included 21 newborns with a diagnose of sepsis plus positive hemoculture, who fulfilled the inclusion and exclusion criteria. The main objective was to determine the etiologic agent of the Neonatal Sepsis at the General Hospital “Isidro Ayora from Loja” in the period January 2015 – June 2016. A data collection form was used to get information from the clinical records. About the study variables, with the following results: the most common causative agent of neonatal sepsis were coagulase negative Staphylococcus (38.1%), followed by Klebsiella pneumoniae (14.3%). Early neonatal sepsis predominated 17%. In early and late neonatal sepsis the causative agent was coagulase negative Staphylococcus. Isolated etiologic agents showed sensitivity to amikacin in 33% and vancomycin. Keywords: Neonatal sepsis, coagulase negative Staphylococcus, Blood culture.